2011
DOI: 10.4161/hv.7.0.14559
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric permeabilization of mammalian dermal tissue for in vivo DNA delivery leads to enhanced protein expression and increased immunogenicity

Abstract: Electropermeabilization of mammalian cells is a technique that has been used for the delivery of therapeutics, such as DNA plasmids or DNA vaccines. Typically, delivery via electropermeabilization occurs through injection of the substance into the tissue of interest followed by the insertion of electrodes at the site and the application of brief electrical pulses. Here we detail a novel and innovative contactless electropermeabilization method to deliver DNA plasmids to dermal tissue in vivo. This process has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…14,15,17 It consists of intratumoral injection of an anti-cancer drug followed by electropermeabilization with invasive electrode delivery device has been reported that may be used to deliver DNA vaccines. 9 That device consists of a high-voltage spark generator producing a spark that travels from an electrode positioned several mm above the targeted area into the skin. The application of multiple sparks likely causes an identical or similar effect as classical electropermeabilization and has been shown to enhance GFP expression in guinea pig skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15,17 It consists of intratumoral injection of an anti-cancer drug followed by electropermeabilization with invasive electrode delivery device has been reported that may be used to deliver DNA vaccines. 9 That device consists of a high-voltage spark generator producing a spark that travels from an electrode positioned several mm above the targeted area into the skin. The application of multiple sparks likely causes an identical or similar effect as classical electropermeabilization and has been shown to enhance GFP expression in guinea pig skin.…”
Section: Discussionmentioning
confidence: 99%
“…In order to generate electric fields of sufficient strength for electroporation to occur, electrodes generally must be in physical contact with the tissue to be electroporated. Methods which do not use contact electrodes, including helium plasma and spark discharge, 8,9 have only been shown to permeabilize skin cells, but not cells in underlying tissue, and their effectiveness in larger animals and humans has not been demonstrated. The use of invasive electrodes such as needle electrodes which are most effective for electroporating cells located in human skin as well as in a variety of underlying tissues has a number of disadvantages: the electrodes must be sterile and must be placed into the tissue uniformly and with sterile technique; insertion of the electrodes and subsequent delivery of electric pulses causes pain; 10 the size of the area and the depth and location of tissue that can be electroporated is quite limited; and side effects such as burns at spots of high current density may occur.…”
Section: Contactless Magneto-permeabilization For Intracellular Plasmmentioning
confidence: 99%
“…Contactless electrodes can consist of a static spark (Broderick et al, 2011a) and make no direct contact with the skin of patients. Examples of noninvasive or surface electrodes are devices such as caliper-type electrodes (Zhang et al, 1996) and the four-plate electrode (4PE; Heller et al, 2007) platform, which use plates as electrodes.…”
mentioning
confidence: 99%
“…When both reached about 0.5 mm, the pain level was not perceptible even at 150 V. The same electrode array was also shown to deliver methotrexate in mice. Recent studies have also reported on contact-less piezoelectric devices to perform electroporation-mediated delivery of vaccines [118]. …”
Section: Electroporationmentioning
confidence: 99%